A biochemical and immunohistochemical study of the effects of caffeic acid phenethyl ester on alveolar bone loss and oxidative stress in diabetic rats with experimental periodontitis. (17th August 2020) - Kızıldağ, Alper; Arabacı, Taner; Albayrak, Mevlüt; Balseven, Havva Müge; Aksu Kızıldağ, Canan; Tasdemir, Ufuk
ABSTRACT: Caffeic acid phenethyl ester (CAPE) is used as a therapeutic agent to prevent bone loss. We determined the effects of systemically administered CAPE on alveolar bone loss and oxidative stress in diabetic rats with experimental periodontitis. Forty male rats were divided into four equal groups: control, experimental periodontitis (EP), EP-diabetes mellitus (EP-DM) and EP-DM-CAPE. DM was induced by streptozotocin, then lipopolysaccharide was injected to induce periodontitis. CAPE was administered to the EP-DM-CAPE group daily for 15 days. Then, serum samples were taken and the rats were sacrificed for histological analyses. Serum interleukin (IL-1β) and oxidative stress also were evaluated. Alveolar bone loss was assessed histomorphometrically. Alveolar bone loss and IL-1β levels were significantly less in the EP-DM-CAPE and EP groups compared to the EP-DM group. Oxidative stress was significantly less in the EP-DM-CAPE group compared to the EP and EP-DM groups. Receptor activator of nuclear factor kappa-B ligand (RANKL) levels were significantly higher in the EP-DM group compared to the disease groups. CAPE significantly reduced RANKL levels in the EP-DM-CAPE group compared to the EP-DM group. We found that CAPE treatment significantly inhibited DM induced oxidative stress and RANKL induced osteoclastogenesis and alveolar bone loss in diabetic rats with periodontitis.